1992
DOI: 10.1128/mcb.12.9.3750
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of rsp-1, a novel cDNA capable of suppressing v-Ras transformation.

Abstract: Using an expression cloning assay, we have isolated a novel cDNA, referred to as rsp-1, which suppresses the v-Ras-transformed phenotype. When introduced into NIH 3T3 fibroblasts under the control of a metallothionein promoter, rsp-i confers resistance to v-Ras, but not to v-Mos or v-Src, and inhibits growth of the cells. The rsp-1 cDNA contains a 831-bp open reading frame encoding a 277-amino-acid leucine-rich protein. The rsp-l cDNA exhibits no significant homology to sequences in the DNA data bases. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 31 publications
3
80
0
Order By: Relevance
“…The RSU1-LIMS1 interaction is notable because it implicates a potential tumor suppressor protein (RSU1) in the integrin signaling pathway. RSU1 was originally identified in a screen for genes that could inhibit Ras-mediated signaling 29 and was later shown to inhibit anchorage-independent growth of MCF7 breast cancer cells 30 . Notably, we have observed that RSU1 is consistently downregulated in prostate cancer 3,24,26 , further suggesting a tumor suppressor role for this gene; however, to date, the mechanism by which RSU1 exerts its effects has not been elucidated.…”
Section: A N a Ly S I Smentioning
confidence: 99%
“…The RSU1-LIMS1 interaction is notable because it implicates a potential tumor suppressor protein (RSU1) in the integrin signaling pathway. RSU1 was originally identified in a screen for genes that could inhibit Ras-mediated signaling 29 and was later shown to inhibit anchorage-independent growth of MCF7 breast cancer cells 30 . Notably, we have observed that RSU1 is consistently downregulated in prostate cancer 3,24,26 , further suggesting a tumor suppressor role for this gene; however, to date, the mechanism by which RSU1 exerts its effects has not been elucidated.…”
Section: A N a Ly S I Smentioning
confidence: 99%
“…RSP-1 is capable of suppressing v-ras transformation in vitro. 41 RSP-1 contains seven leucine-rich repeats, like LRRC2. Thus, there are both functional and positional reasons to study this gene further with regard to its possible role in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly a number of ras-speci®c suppressors have been described previously (SchaÈ fer, 1994). For example, Rsu-1 speci®cally blocks ras transformation (Cutler et al, 1992). NIH3T3 cells expressing p33 rsu-1 have been shown to resist transformation by retroviruses containing v-ki-ras and v-Ha-ras genes, but were susceptible to v-src and v-mos containing viruses.…”
Section: Growth Propertiesmentioning
confidence: 99%